UPAYA PEWARISAN TARI BUAI- BUAI DI NAGARI PAUH IX KELURAHAN KURANJI KECAMATAN KURANJI KOTA PADANG - Dede Putri Perdani; Indrayuda Indrayuda; Herlinda Mansyur (SENDRATASIK UNP, 2018)
Abstract This article aims to reveal and describe the efforts of the Inheritance of Buai-Buai Dance in Nagari Pauh IX, Kelurahan Kuranji, Kecamatan Kuranji, and Padang City.This type of research was qualitative research, using descriptive methods. This research instrument was the researcher. Techniques of data collection were carried out by using literature study, observation, interview and documentation. Data analysis was carried out by data reduction steps, carrying out data display/data preparation and drawing verification conclusions. The results show that the Buai-Buai Dance is almost extinct due to the number of heirs who were getting old. An effort to inherit the Buai-Buai dance is performed by the Minang Saiyo studio which is by providing training to the community as the next generation. Keywords: Inheritance, Buai-Buai Dance